Vapor pressure and enthalpy of vaporization of oil of catnip by correlation gas chromatography. (January 2016) - Simmons, Daniel; Gobble, Chase; Chickos, James
Highlights: Vaporization enthalpies of the nepetalactones from oil of catnip have been evaluated. Vapor pressures from T = (298.15 to 350) K have been evaluated. Oil of catnip has a vapor pressure similar to DEET at T = 298.15 K. Abstract: The vaporization enthalpy and vapor pressure of the two nepetalactones found in Nepeta cataria have been evaluated by correlation gas chromatography. Vaporization enthalpies at T = 298.15 K of (68.0 ± 1.9) and (69.4 ± 1.9) kJ ⋅ mol −1 have been derived for the minor diastereomer, (4aS, 7S, 7aS)-nepetalactone, and major one, (4aS, 7S, 7aR)-nepetalactone, respectively. Vapor pressures also at T = 298.15 K of p = (1.2 ± 0.04) Pa and (0.91 ± 0.03) Pa have been evaluated for the minor and the major stereoisomer. In addition to being of interest because of the remarkable effect it has on various felids, oil of catnip is also quite effective in repelling mosquitoes, comparable to diethyl-m-toluamide (DEET). The vapor pressures evaluated in this work suggest that the two stereoisomers have similar volatility to DEET at ambient temperatures.